2012
DOI: 10.1111/febs.12036
|View full text |Cite
|
Sign up to set email alerts
|

How is the distal pocket of a heme protein optimized for binding of tryptophan?

Abstract: Indoleamine 2,3-dioxygenase and tryptophan 2,3-dioxygenase catalyze the O 2 -dependent oxidation of L-tryptophan to N-formylkynurenine. Both are heme-containing enzymes, with a proximal histidine ligand, as found in the globins and peroxidases. From the structural information available so far, the distal heme pockets of these enzymes can contain a histidine residue (in tryptophan 2,3-dioxygenases), an arginine residue and numerous hydrophobic residues that line the pocket. We have examined the functional role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…According to a series of studies employing human IDO1 variants, Ser167 is not regarded to be essential for substrate binding . Indeed, S167A and S167H variants of human IDO1 showed high affinity for l ‐Trp (low K m for l ‐Trp: 21 μ m ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a series of studies employing human IDO1 variants, Ser167 is not regarded to be essential for substrate binding . Indeed, S167A and S167H variants of human IDO1 showed high affinity for l ‐Trp (low K m for l ‐Trp: 21 μ m ) .…”
Section: Resultsmentioning
confidence: 99%
“…According to a series of studies employing human IDO1 variants, Ser167 is not regarded to be essential for substrate binding [17,18,31]. Indeed, S167A and S167H variants of human IDO1 showed high affinity for L-Trp (low K m for L-Trp: 21 lM) [31]. Even in the present study, mouse and platypus IDO1 S171T variants still retain a rather high affinity for L-Trp, although their K m values are 2.8-to 4.5-fold higher than that of wild-types.…”
Section: Evolution Of Vertebrate Idosmentioning
confidence: 99%
“…The determinants of substrate binding in these proteins have been probed in molecule detail using sitedirected mutagenesis, 61 following similar detailed studies in peroxidases. 62 These observations are relevant for this study, since spectroscopy has been used to quantify this binding in the dioxygenases.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Chauhan et al . reported that a Phe163Ala variant shows a drastic decrease in k cat and that approximately 130‐ and 500‐fold increases in K m are observed in Phe163Ala and Arg231Lys variants, respectively. These results suggested that these three residues are crucial for human IDO1 activity.…”
Section: Introductionmentioning
confidence: 99%